PENGARUH STRATEGI PEMBELAJARAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR KONSTRUKSI POLA PADA SISWA SMK NEGERI 8 MEDAN - Surniati Chalid (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
Vocational schools (SMK) is a secondary education that preparesstudents primarily for working on a particular field. Diverse efforts made by SMKgraduates increased 8 Medan include improving the quality of education byreforming both the substance of the material and the provision of facilities andinfrastructure. However, the results have not been up, cermatan can be seen fromthe low competence of graduates, making it less able to play a role in meeting thedemands of the workplace. Assumed to be an indication of the quality of learning isstill performed during less effective, less efficient and unable to increase studentinterest. In order to achieve maximum learning outcomes is through theimprovement of learning strategies to utilize the educational facilities in accordancewith existing conditions, ie, by examining one of the subjects namely Constructiondressmaking pattern. Construction material pattern done with learning strategyapproach manipulated into two comparing results STAD cooperative learningstrategies and learning strategies expository and compare the results with thelearning characteristics of students with high and low interest in learning onlearning outcomes Pattern Construction.